Perioperative Myocardial Infarction After Coronary Artery Bypass Grafting: How to Identify? - Diah Ivana Sari; Setyasih Anjarwani; Ardian Rizal (Heart Science Journal, 2023)
Introduction. Perioperative myocardial infarction (PMI) associated with the surgical revascularization (CABG) occurs in about 3–5% of patients. Myocardial necrosis and ischaemia after CABG are caused by direct cardiac trauma from manipulation, reperfusion injury, incomplete revascularization, hypotension, bleeding, ventricular arrhythmia, acute graft closure, inadequate perioperative myocardial protection and others.Case report. The introduced case report explains the rupture of right ventricle result in periprocedural myocardial infarction following the surgical myocardial revascularization. 62-year-old man has undergone the coronary bypass surgery with arterial graft of left mammary artery (LIMA) to left anterior descending artery (LAD) and savenous graft to left circumflex coronary artery (LCx). Early in the post-surgery period a perioperative myocardial infarction (PMI) developed, with laboratory correlation of cardio-specific enzymes elevation and ECG changes in terms of ischaemia in the diaphragmatic region. Echocardiography showed akinesia of the apex, apical septal and apical inferior segments accompanied by the decrease in ejection fraction (EF) of the left ventricle.Conclusion. Early detection of PMI may therefore, prompt institution of therapeutic measures to relieve the ischaemia and decrease the incidence and the size of PMIKey words: Perioperative Myocardial Infarction, CABG